Electrophoretic measurement of zeta potential of needle-generated gas bubble in aqueous solutions in the presence of collectors - Pascual, Juan Inocencio M.; Mendoza, Herman D. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This study aims to measure the zeta potential of gas-bubbles in aqueous solution with potassium nitrate (KNO3) as supporting electrolyte in the absence and presence of collectors namely potassium amyl xanthate (PAX) as anionic collector and cetyltrimethylammonium bromide (CTAB) as cationic collector at varying pH. A modified electrophoretic set-up was fabricated to generate microbubbles by controlled pressure through a microneedle. The gas-bubbles move in a parabolic motion towards the electrode they are attracted to. Only the horizontal component or the electrophoretic mobility was considered in calculating the zeta potential using the Smoluchowski's equation. Results showed that in the electrolyte solutions without collectors, the isoelectric point (i.e.p.) was found to be around pH 3.8. As the solution reached alkalinity, magnitude of the zeta potential increased due to the increased amounts of hydroxyl ions thus the abundance of charges at the bubble's surface. An increase in PAX's concentration resulted in an increase in magnitude of the zeta potential of gas-bubbles with increasing pH due to the favorable interactions of the negative surface charges, nature of the hydrophobicity of the collector and the increase in electrophoretic mobility due to the decrease of boundary layer volume of the bubble. Consequently, as CTAB's concentration was increased, zeta potential of the bubble also increased in magnitude. As pH increased, however, the zeta potential decreased as a result of the boundary layer reaching a greater thickness for the formation of an expanded diffuse layer and thus increased the friction with the liquid side.
Thesis (Master of Science in Metallurgical Engineering)--University of the Philippines Diliman
Keywords: Flotation; Electrophoresis; Gas bubbles